Comparison of the Effectiveness of Cognitive-Behavioral Education Based on Procrastination and Cognitive Motivational Multidimensional Intervention on Self-Efficacy of Students with Addicted Parents - Parisa Nematzadeh sote; Hosssein ali Qanadzadegan; Seyedeh olia Emadian (Iranian Journal of Educational Research)
Objective: The current investigation was carried out to compare the efficacy of cognitive-behavioral education centered on procrastination and motivational-cognitive multidimensional intervention on the self-efficacy of students with addicted parents at the high schools of Babolsar. Methods: The study employed a semi-experimental research design with pre-test, post-test, and follow-up assessments using an unequal control group. The target population consisted of all students with addicted parents at the high schools in Babolsar and their parents in 2022. A total of 45 individuals were purposively chosen and assigned to two experimental groups and a control group, each comprising 15 participants. The research questionnaires were administered, and cognitive-behavioral training focusing on procrastination and motivational-cognitive multidimensional intervention was conducted for the experimental groups, while the control group was placed on the waiting list for the intervention. Results: The findings indicated that both interventions were effective in enhancing academic self-efficacy. Moreover, the impact of cognitive-behavioral training based on procrastination was found to be superior to motivational-cognitive multidimensional intervention in terms of academic self-efficacy enhancement. Conclusions: In conclusion, both interventions exhibit potential for enhancing students' self-efficacy levels.